Empowering Indigenous Papuan Communities for Early Flood Emergency Response: A Quasi-Experimental Study in Entrop, Indonesia - Soalihin Soalihin; Suselo Suselo; Asmawi Asmawi; Iin Aryani; Nur Hamdani Nur (Pancasakti Journal Of Public Health Science And Research, 2026)
Floods are one of the most frequent disasters in Indonesia and have a significant impact on the safety, health, and livelihoods of communities, including in Papua Province. The unique geographic and climatic conditions make this region vulnerable to flooding, necessitating a rapid and appropriate emergency response. Indigenous Papuans possess local wisdom, such as knowledge of natural signs, the value of mutual cooperation, and the role of traditional leaders, which offer significant potential in disaster management. However, this initial response capacity needs to be continuously strengthened to ensure more effective flood emergency management. This study aims to evaluate the effectiveness of empowering indigenous Papuans in improving the initial emergency response to floods in Entrop Village, South Jayapura District. The study used a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 41 indigenous Papuans who had experienced flooding, selected using the Slovin formula from a total population of 69. The intervention was conducted through outreach and digital simulations in the form of flood disaster videos. The results showed that the average emergency response score increased from 0.51 in the pretest to 0.73 in the posttest, a difference of 0.22. This increase indicates a significant improvement in the community's ability to recognize flood risks, determine priority actions, and carry out a more appropriate initial response. These findings confirm that empowerment based on the integration of modern disaster knowledge and local wisdom is effective in strengthening the preparedness of indigenous communities as the frontline in handling initial flood disasters in Papua.